Riverine barrier and aridity effects on taxonomic, phylogenetic and functional diversities of lizard assemblages from a semi‐arid region. (28th April 2022) - Gonçalves‐Sousa, José Guilherme; de Fraga, Rafael; Menezes, Bruno Sousa; Mesquita, Daniel Oliveira; Ávila, Robson Waldemar
Abstract: Aim: Disentangling historical and ecological effects on different components of species diversity is key to understanding the assembly and maintenance of communities over space and time. Historical factors may be stronger predictors of the community composition at regional scales, while ecological factors may be more important predictors at local scales. Here, we evaluate multiple biodiversity dimensions to investigate riverine barrier and aridity effects on the assembly and structure of lizard assemblages. Location: Semi‐arid region of northeastern Brazil. Taxon: Lacertilia (lizards). Methods: We used data describing 63 lizard assemblages from Caatinga habitats to investigate the effects of a riverine barrier and eight environmental gradients on estimates of taxonomic, phylogenetic and functional diversity. At the regional scale, we compared communities between the banks of the SFr, assuming that differences could emerge from regionally interrupted dispersal in some of the sampled species. At local scales, we evaluated the patterns of phylogenetic and functional structure of the lizard assemblages from Caatinga, and investigated the influence of aridity‐related gradients on species richness, taxonomic, phylogenetic and functional diversity. Results: Lizard assemblages were regionally structured by the SFr acting as a barrier to 47% of the species sampled. We detected phylogenetic signal in 88% of the functional traits. Lizard assemblages were phylogenetic and functionally overdispersed. Moreover, we detected evidence of aridity gradients intensifying the overdispersion of phylogenies and functional traits. Main conclusions: Lizard assemblages showed high variation at both regional and local scales. Riverine barriers played a stronger role as a historical factor structuring assemblages on a regional scale. The interaction of historical constraints with competition enhanced by aridity on a local scale may play a role in structuring lizard assemblages across multiple scales.